Extracellular membrane vesicles from umbilical cord blood‐derived MSC protect against ischemic acute kidney injury, a feature that is lost after inflammatory conditioning. Issue 1 (10th December 2013) - Kilpinen, Lotta; Impola, Ulla; Sankkila, Lotta; Ritamo, Ilja; Aatonen, Maria; Kilpinen, Sami; Tuimala, Jarno; Valmu, Leena; Levijoki, Jouko; Finckenberg, Piet; Siljander, Pia; Kankuri, Esko; et al.
Abstract : Background: Mesenchymal stromal cells (MSC) are shown to have a great therapeutic potential in many immunological disorders. Currently the therapeutic effect of MSCs is considered to be mediated via paracrine interactions with immune cells. Umbilical cord blood is an attractive but still less studied source of MSCs. We investigated the production of extracellular membrane vesicles (MVs) from human umbilical cord blood derived MSCs (hUCBMSC) in the presence (MVstim) or absence (MVctrl) of inflammatory stimulus. Methods: hUCBMSCs were cultured in serum free media with or without IFN‐γ and MVs were collected from conditioned media by ultracentrifugation. The protein content of MVs were analyzed by mass spectrometry. Hypoxia induced acute kidney injury rat model was used to analyze the in vivo therapeutic potential of MVs and T‐cell proliferation and induction of regulatory T cells were analyzed by co‐culture assays. Results: Both MVstim and MVctrl showed similar T‐cell modulation activity in vitro, but only MVctrls were able to protect rat kidneys from reperfusion injury in vivo. To clarify this difference in functionality we made a comparative mass spectrometric analysis of the MV protein contents. The IFN‐γ stimulation induced dramatic changes in the protein content of the MVs. Complement factors (C3, C4A, C5) and lipid binding proteins (i.e apolipoproteins) were only found in the MVctrls, whereas the MVstim contained tetraspanins (CD9, CD63, CD81) and more complete proteasome complex accompanied with MHCI. We further discovered that differently produced MV pools contained specific Rab proteins suggesting that same cells, depending on external signals, produce vesicles originating from different intracellular locations. Conclusions: We demonstrate by both in vitro and in vivo models accompanied with a detailed analysis of molecular characteristics that inflammatory conditioning of MSCs influence on the protein content and functional properties of MVs revealing the complexity of the MSC paracrine regulation.